Criteria Requirement for IBS Vendor Selection - Ahmad Taufik Nursal; Mohd Faizal Omar; Mohd Nasrun Mohd Nawi (International Journal of Supply Chain Management, 2016)
The role of vendor selection in construction procurement was addressed as a crucial process to achieve project objective not only in conventional construction project, but also in IBS project. Due to the promising advantages of IBS, constructions industry has witness numerous of IBS vendor available in Malaysia market. This situation has created a decision problem among the construction company to select the best vendor that fulfils the project need. Several complexities of construction vendor selection were discussed in past studies. Thus, there is a need of decision aid in IBS vendor selection. A discussion of criteria in construction vendor selection has also been presented. As initial step to develop a decision model, a documental analysis was performed to gather the related IBS vendor selection criteria. Literature suggest that construction vendor selection can be grouped into cost, quality, service, buyer and vendor relationship, assurance supply, payment term, and past performance. After gather and filtering criteria from literature, 38 criteria were found related with IBS vendor selection. This set of criteria is essential to further develop research instrument to identify the criteria of IBS vendor selection in the next phase of research.